2005
DOI: 10.1002/zoo.20062
|View full text |Cite
|
Sign up to set email alerts
|

Female age-specific reproductive rates, birth seasonality, and infant mortality of ring-tailed Lemurs on St. Catherines Island: 17-year reproductive history of a free-ranging colony

Abstract: To compare reproductive parameters of a managed population of free-ranging provisioned ring-tailed lemurs (Lemur catta) to wild L. catta populations, we analyzed birth and mortality records collected over the 17-year history of the St. Catherines Island ring-tailed lemur colony. The majority of births in this colony (approximately 80%) occurred in March, which indicates that most females at this site conceived during the first estrus cycle of the breeding season, as do wild ring-tailed lemur females (Sauther [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(74 citation statements)
references
References 31 publications
2
72
0
Order By: Relevance
“…Infants are physically active within days of birth; they may begin climbing branches within 2 weeks and may begin eating solid foods before 2 months of age (Jolly 1966). Infant mortality may be as high as 50% in a given population (Gould et al 2003) but this often relates to the age of the mother, environmental conditions, and developmental state (Benirscke and Miller 1981;Gould et al 2003;Koyama et al 2001;Parga and Lessnau 2005). Neonatal mortality within the 1st month accounts for about one-third of all infant deaths .…”
Section: Ontogeny and Reproductionmentioning
confidence: 99%
“…Infants are physically active within days of birth; they may begin climbing branches within 2 weeks and may begin eating solid foods before 2 months of age (Jolly 1966). Infant mortality may be as high as 50% in a given population (Gould et al 2003) but this often relates to the age of the mother, environmental conditions, and developmental state (Benirscke and Miller 1981;Gould et al 2003;Koyama et al 2001;Parga and Lessnau 2005). Neonatal mortality within the 1st month accounts for about one-third of all infant deaths .…”
Section: Ontogeny and Reproductionmentioning
confidence: 99%
“…It has been reported that twinning is common among H. alaotrensis, a close congener of H. meridionalis (Steyn and Feistner, 1994;Beattie and Feistner, 1998;Mutschler et al, 2000), and while it is less frequent among H. griseus (Haring and Davis, 1998), twinning is known to occur (Tan, 2000). Although lemurs are known for their high-frequency of multifetal pregnancies similar to some callitrichid primates (Bales et al, 2001;Harris et al, 2014), these also result in high infant mortality (Debyser, 1995;Parga and Lessnau, 2005;Volampeno et al, 2011). In some cases an accidental fall may cause or lead to death in a neonate (Morland, 1990), yet stillborn and infant mortality have been shown to increase with multifetal births, often with stress and infections linked to infant/juvenile mortality (Debyser, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Dizygotic twinning is much more common than monozygotic twinning in humans (Hoekstra et al, 2008) and is known to occur in other non-human primates (Geissmann, 1990;Ely et al, 2006;Harris et al, 2014). Twinning rates among haplorrhine primates are low (e.g., Geissmann, 1990;Link et al, 2006;Huck et al, 2014;but see Bales et al, 2001 for an example of callitrichid twinning), however, it appears to be extremely common in primates with a bicornuate uterus, such as in Strepsirrhini, i.e., a suborder of Primates which includes lemurs, lorises, and galagos (Pasztor and van Horn, 1976;van Horn and Eaton, 1979;Benirschke and Miller, 1982;Parga and Lessnau, 2005;Tecot et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A second or third pair of nipples could facilitate nursing twins, although wild ring-tailed lemurs usually give birth to only 1 infant [Koyama et al, 2001;Jolly et al, 2002;Gould et al, 2003]. In semicaptive conditions, twins are frequent, and even triplets occur, but usually only 1 of the infants survives [Parga and Lessnau, 2005]. Athelia is very rare and is usually associated with a variety of other conditions.…”
Section: Variation In Nipple Numbermentioning
confidence: 99%
“…Female 167 successfully gave birth to her first infant in 2005 and, although she subsequently lost her infant, she appears reproductively normal. Given that younger female ring-tailed lemurs (3-4 years of age) experience high frequencies of infant mortality [Sauther, 1991;Sussman, 1991;Parga and Lessnau, 2005], it is unlikely her infant's death was related to this variation.…”
Section: Virilizationmentioning
confidence: 99%